1993
DOI: 10.1111/j.1476-5381.1993.tb13779.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of platelet‐activating factor on the responsiveness of the human nasal airway

Abstract: 1 The effects of inhaled platelet-activating factor (PAF) on responsiveness of the human nasal airway were examined in normal subjects by measuring nasal airway resistance in response to histamine and bradykinin at 2, 6, 24, 48 h and 7 d after PAF administration. Eosinophil cationic protein (ECP) in nasal secretions was also measured.2 Intranasal aerosol administration of PAF, 30 or 60 fig per nostril to normal human subjects induced an increased responsiveness to inhaled histamine, 50 to 400 1ig and bradykini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…56 Human PAF nasal provocation leads to increased nasal airway resistance, reduced nasal volume, and symptoms of nasal obstruction. [57][58][59] Biochemically, PAF challenge results in nasal hyperresponsiveness to histamine and kinins and recruitment of neutrophils and eosinophils to the nasal mucosa. 58,60,61 PAFRs are expressed in nasal mucosal epithelial cells, submucosal glands, vascular endothelial cells, mast cells, leukocytes, and lymphocytes.…”
Section: Allergic Rhinitis and Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…56 Human PAF nasal provocation leads to increased nasal airway resistance, reduced nasal volume, and symptoms of nasal obstruction. [57][58][59] Biochemically, PAF challenge results in nasal hyperresponsiveness to histamine and kinins and recruitment of neutrophils and eosinophils to the nasal mucosa. 58,60,61 PAFRs are expressed in nasal mucosal epithelial cells, submucosal glands, vascular endothelial cells, mast cells, leukocytes, and lymphocytes.…”
Section: Allergic Rhinitis and Asthmamentioning
confidence: 99%
“…[57][58][59] Biochemically, PAF challenge results in nasal hyperresponsiveness to histamine and kinins and recruitment of neutrophils and eosinophils to the nasal mucosa. 58,60,61 PAFRs are expressed in nasal mucosal epithelial cells, submucosal glands, vascular endothelial cells, mast cells, leukocytes, and lymphocytes. 62 In animal models of allergic rhinitis, PAFR antagonists reduce nasal airway resistance and vascular permeability after allergen challenge.…”
Section: Allergic Rhinitis and Asthmamentioning
confidence: 99%
“…51 The re sulting AHR is similar, in many w ays, to that observe d in allergic rhinitis , as PAF also c ause s a signific ant nasal ne utrophilia and eosinophilia, toge the r w ith raise d ECP levels in nasal lavage fluid. [52][53][54] Although PAF c an induc e AHR in the human nasal airw ay, its role in allergen-induced AHR is less de fine d. Antige n challenge w ith grass polle n in atopic indiv iduals w ith SAR causes the release of lyso-PAF and PAF, 41,55 but it is uncle ar w he ther PAF or lyso-PAF are release d in PAR, 56 One possibility is that any PAF generate d is c onve rte d to lyso-PAF by acetylhydrolase present in the lavage fluid. The ac tivity of this enzyme in lavage fluid is signific antly rais ed follow ing grass polle n challenge in sensitive subje cts.…”
Section: Platelet Activating Factor (Paf)mentioning
confidence: 97%
“…50 In normal, non-atopic subjects, it induce s a nasal AHR to histamine and bradykinin 51,52 and causes an inc re ased re sponse to polle n in subjec ts w ith SAR. 51 The re sulting AHR is similar, in many w ays, to that observe d in allergic rhinitis , as PAF also c ause s a signific ant nasal ne utrophilia and eosinophilia, toge the r w ith raise d ECP levels in nasal lavage fluid.…”
Section: Platelet Activating Factor (Paf)mentioning
confidence: 99%
“…We have investigated the possible involvement of PAF in allergic rhinitis, and have found that PAF can be released, along with its precursor/metabolite lyso-PAF, in nasal lavage fluids during the early antigen-induced reaction in patients with respiratory allergy [2]. Nasal challenge with PAF provokes nasal obstruction with an increase in nasal airway resistances [3], and nasal hyperreactivity [4,5]. Furthermore, nasal neutrophilia and eosinophilia have been observed after challenge with PAF, with a more rapid and more marked response in atopic than in normal subjects [6].…”
mentioning
confidence: 99%